Absence of localization of Fourier-Laplace series - Rasedee, Ahmad Fadly Nurullah; Rakhimov, Abdumalik; Ahmedov, Anvarjon A.; Ishak, Norizarina; Hamzah, Siti Raihana (American Institute of Physics, 2017)
This article investigates a function f(x), constructed from the Nikol’skii class in S2. The estimation obtained will show that the Riesz mean of the spectral expansions is unable to be strengthened due to absence of localization caused by a singualrity at a definite point f(x), on the sphere